Defining combat helmet coverage for protection against explosively propelled fragments. Issue 1 (26th July 2013) - Breeze, John; Baxter, D; Carr, D; Midwinter, M J
Abstract : Introduction: Prevention against head wounds from explosively propelled fragments is currently the Mark 7 general service combat helmet, although only limited evidence exists to define the coverage required for the helmet to adequately protect against such a threat. The Royal Centre for Defence Medicine was tasked by Defence Equipment and Support to provide a framework for determining the optimum coverage of future combat helmets in order to inform the VIRTUS procurement programme. Method: A systematic review of the literature was undertaken to identify potential solutions to three components felt necessary to define the ideal helmet coverage required for protection against explosively propelled fragments. Results: The brain and brainstem were identified as the structures requiring coverage by a helmet. No papers were identified that directly defined the margins of these structures to anatomical landmarks, nor how these could be related to helmet coverage. Conclusions: We recommend relating the margins of the brain to three identifiable anatomical landmarks (nasion, external auditory meatus and superior nuchal line), which can in turn be related to the coverage provided by the helmet. Early assessments using an anatomical mannequin indicate that the current helmet covers the majority of the brain and brainstem from projectiles with a horizontal trajectory but not from ones that originate from the ground. Protection from projectiles with ground-originating trajectories is reduced by helmets with increased stand-off from the skin. Future helmet coverage assessments should use a finite element numerical modelling approach with representative material properties assigned to intracranial anatomical structures to enable differences in projectile trajectory and helmet coverage to be objectively compared.